Low-density impact-resistant C / SiC ceramic composite material and preparation method thereof

By preparing low-density, impact-resistant C/SiC ceramic composite materials and utilizing the combination of chitosan with carbon fiber braids and silicon powder, the problems of structural stability and thermal conductivity of C/SiC ceramic composite materials in photovoltaic panels were solved, achieving high-temperature resistance to deformation and heat dissipation, and improving the impact toughness and tensile strength of the material.

CN121318459APending Publication Date: 2026-01-13HUBEI SANJIANG HANGTIAN JIANGBEI MASCH ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511311989.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing C/SiC ceramic composite materials are difficult to withstand the drastic temperature cycles of the external environment in photovoltaic panels, resulting in insufficient structural stability, and their resistance to deformation and thermal conductivity at high temperatures need to be improved.

Method used

Low-density, impact-resistant C/SiC ceramic composite materials were prepared by reactive melt infiltration using a premix of carbon fiber braided material, silicon powder, and chitosan. Chitosan was used as a carbon source and silicon carbide raw material to improve interfacial bonding and thermal conductivity, thereby reducing density.

Benefits of technology

The material has high impact toughness and high tensile strength at high temperatures, which can effectively dissipate heat, reduce the temperature of the solar panel, and ensure that the irregular structure does not deform during processing. The product is basically formed to net dimensions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121318459A_ABST
    Figure CN121318459A_ABST
Patent Text Reader

Abstract

The invention discloses a low-density impact-resistant C / SiC ceramic composite material and a preparation method thereof. The method comprises the following steps: providing a carbon fiber woven body and a premix compounded by silicon powder, first chitosan and zirconium carbide powder; mixing the carbon fiber woven body with second chitosan, and then performing pretreatment to obtain a C / C blank; the low-density impact-resistant C / SiC ceramic composite material is obtained by taking a C / C blank and a premix as raw materials through a reactive infiltration method. The C / SiC ceramic composite material can resist high temperature accumulated due to long-time sunlight radiation in a photovoltaic cell panel, has good heat conduction capability, and can continuously dissipate heat to the surrounding environment, so that the temperature of a cell panel assembly is reduced. Compared with a traditional C / SiC ceramic composite material, the C / SiC ceramic composite material has higher impact toughness, high-temperature tensile strength and heat conductivity and lower density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of C / SiC ceramic composite material molding technology, and in particular to a low-density, impact-resistant C / SiC ceramic composite material and its preparation method. Background Technology

[0002] In the past decade or so, with the accelerated shift of energy development towards green and low-carbon directions, photovoltaic power generation has been continuously increasing and expanding. However, only 5% to 25% of the solar radiation energy absorbed by photovoltaic panels is converted into electrical energy, resulting in extremely low efficiency. The photoelectric efficiency of photovoltaic panels is affected by surface temperature, reaching a minimum at a radiation intensity of 1000 W / m². 2 Under sunlight, once the surface temperature of the solar panel exceeds 25°C, the photoelectric efficiency decreases by about 0.4% for every degree Celsius increase. Under prolonged exposure to solar radiation, the structural components of the photovoltaic panel module will be damaged due to high temperatures, further reducing the photoelectric conversion efficiency.

[0003] C / SiC ceramic composites (carbon fiber reinforced silicon carbide composites) possess high strength, high modulus, ablation resistance, and good high-temperature mechanical properties, making them suitable for cutting-edge fields such as photovoltaics. However, existing C / SiC ceramic composites suffer from inherent brittleness, making it difficult to withstand the drastic temperature cycling of the external environment when applied to photovoltaic panels. Furthermore, the internal thermal stress generated during operation can lead to insufficient structural stability under long-term service conditions.

[0004] Therefore, it is of great significance to provide a new C / SiC ceramic composite material that is resistant to thermal shock, deformation at high temperatures, and has good thermal conductivity as a structural component for photovoltaic solar panel modules. Summary of the Invention

[0005] The purpose of this invention is to overcome the above-mentioned technical deficiencies and propose a low-density impact-resistant C / SiC ceramic composite material and its preparation method, thereby solving the technical problems that the thermal shock resistance, high-temperature deformation resistance, and thermal conductivity of C / SiC ceramic composite materials in the prior art need to be improved.

[0006] In a first aspect, the present invention provides a method for preparing a low-density, impact-resistant C / SiC ceramic composite material, comprising the following steps: S1. Provides carbon fiber braided fabric and premixed material composed of silicon powder, first chitosan and zirconium carbide powder; S2. The carbon fiber braid and the second chitosan are mixed and then pretreated to obtain a C / C preform; S3. Using C / C billets and premixes as raw materials, low-density impact-resistant C / SiC ceramic composite materials are obtained through reactive melting infiltration.

[0007] In a second aspect, the present invention provides a low-density impact-resistant C / SiC ceramic composite material, which is obtained by the preparation method of the low-density impact-resistant C / SiC ceramic composite material provided in the first aspect of the present invention.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The C / SiC ceramic composite material of this invention can resist the high temperatures accumulated in photovoltaic panels due to prolonged solar radiation, while also possessing excellent thermal conductivity, continuously dissipating heat to the surrounding environment and thus reducing the temperature of the panel assembly. Compared with traditional C / SiC ceramic composite materials, the C / SiC ceramic composite material of this invention has higher impact toughness, high-temperature tensile strength (strong resistance to deformation at high temperatures), thermal conductivity, and lower density. The method of this invention ensures that irregularly shaped structures undergo minimal deformation during subsequent machining, and the product is essentially formed to net dimensions. Attached Figure Description

[0009] Figure 1 This is a schematic diagram of the braided structure in the irregularly shaped component for photovoltaic generator prepared according to Embodiment 1 of the present invention. Detailed Implementation

[0010] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0011] In a first aspect, the present invention provides a method for preparing a low-density, impact-resistant C / SiC ceramic composite material, comprising the following steps: S1. Provides carbon fiber braided fabric and premixed material composed of silicon powder, first chitosan and zirconium carbide powder; S2. The carbon fiber braid and the second chitosan are mixed and then pretreated to obtain a C / C preform; S3. Using C / C billets and premixes as raw materials, low-density impact-resistant C / SiC ceramic composite materials are obtained through reactive melting infiltration.

[0012] This invention solves the problem of high cost in the preparation of C / SiC ceramic composites by using chitosan, which is widely available and inexpensive, as a carbon source, thus facilitating large-scale industrial production. Simultaneously, chitosan, being a macromolecule, can form hydrogen bonds between the amino hydrogen atoms on its sugar ring units and the oxygen atoms on its six-membered rings. Furthermore, during ball milling and blending, it spontaneously forms microspheres with micron-sized structures, autonomously encapsulating silicon powder and zirconium carbide powder. Through physical interactions and chemical bonds, it solves the problem of matrix phase dispersion, improving product quality consistency. In addition, the chitosan of this invention is added in two stages, improving the isotropy of the low-density impact-resistant C / SiC ceramic composite, resulting in higher mechanical properties. Specifically, in step S2, the chitosan, as a carbon source, is treated at high temperature to form a carbon layer coating the surface of the carbon fiber braid, improving the interfacial bonding between silicon carbide / zirconium carbide and the carbon fiber braid, preventing fiber pull-out under external forces, and improving the product's mechanical properties. In step S3, the chitosan is introduced into the low-density impact-resistant C / SiC ceramic composite as a raw material for silicon carbide. This invention shortens the preparation time and improves production efficiency through integrated melt infiltration and embedding molding technology.

[0013] In this embodiment, the molecular weight range of the first chitosan and the second chitosan is 20,000 to 50,000.

[0014] In this embodiment, in step S1, the carbon fiber braid is a braided body with a certain geometric shape, structure, and fiber orientation, made by textile processes (such as weaving, knitting, sewing, winding, etc.) of carbon fibers (such as carbon fiber cloth, carbon fiber mesh, carbon fiber bundles, etc.). This invention does not limit the shape of the braided body; those skilled in the art can select it according to the actual situation.

[0015] In this embodiment, the density of the carbon fiber braid is 0.55~0.75 g / cm³. 3 Including but not limited to 0.55g / cm 3 0.6g / cm 3 0.65g / cm 3 0.7g / cm 3 0.75g / cm 3 wait.

[0016] In this embodiment, in step S1, the mass ratio of silicon powder to the first chitosan in the premix is ​​1:(0.05~0.15). If the mass ratio of silicon powder to the first chitosan is too low, the overall oxygen content of the product will be too high, resulting in lower overall material performance. If the mass ratio of silicon powder to the first chitosan is too high, the silicon powder will agglomerate, the phase will be unevenly dispersed, and the reaction and infiltration effect between the matrix will be poor, which will also have an adverse effect on the overall material performance.

[0017] In this embodiment, in step S1, the mass ratio of silicon powder to zirconium carbide powder in the premix is ​​1:(0.05~0.15).

[0018] In this embodiment, in step S1, the premix is ​​obtained by grinding silicon powder, first chitosan, and zirconium carbide powder until uniform.

[0019] Preferably, the premixed material is dried and stored for later use.

[0020] In this embodiment, in step S2, the mass ratio of carbon fiber braid to second chitosan is 1:(0.1~0.3). If the proportion of second chitosan is too low, the chitosan will not be completely dispersed throughout the braid, resulting in an uneven carbon layer and affecting the performance of subsequent products. If the proportion of second chitosan is too high, the oxygen content will be too high, and large-area pores will be generated, affecting the performance of the products.

[0021] In this embodiment, step S2 includes: mixing carbon fiber braid and second chitosan, followed by hot pressing and a first heat treatment to obtain a C / C blank.

[0022] The hot-pressing process includes fixing the mixture of carbon fiber braid and chitosan in a first mold, applying a pressure of 3-6 MPa, and slowly heating to 200-220°C, so that the molten chitosan fully impregnates the carbon fiber braid and remains inside the carbon fiber braid.

[0023] Preferably, the first mold is a graphite tooling mold.

[0024] The first heat treatment process includes: heating to 400-500℃ at a heating rate of 2-3℃ / min, heating to 950-1050℃ at a heating rate of 1.5-2.0℃ / min, heating to 1500-1600℃ at a heating rate of 1.0-1.5℃ / min, heating to 2000-2100℃ at a heating rate of 0.5-1.0℃ / min, and holding at that temperature for 140-160 minutes; during the first heat treatment, a protective atmosphere is introduced. This invention does not limit the type of protective atmosphere, and those skilled in the art can select it according to the actual situation. For example, the protective atmosphere can be nitrogen or argon, etc.

[0025] Preferably, during the process of introducing the protective atmosphere, the gas flow rate is 1~2.5L / min, and the furnace is kept under a slightly positive pressure (2~7kPa).

[0026] Preferably, prior to the first heat treatment, the process further includes alternating between vacuuming and introducing a protective atmosphere to purge air from the furnace, specifically: The carbon fiber braid and the composite of the second chitosan were transferred to the graphitization chamber and evacuated to below 200 Pa. Then a protective atmosphere is introduced until the vacuum level reaches above 95 kPa; Repeat the above process of evacuation and introduction of protective atmosphere 2 to 5 times.

[0027] In this embodiment, in step S3, the mass ratio of C / C blank to premix is ​​1:(1.1~1.3). If the proportion of premix is ​​too low, the product appearance will be poor, with obvious defects such as pores and pits; if the proportion of premix is ​​too high, the premix will agglomerate and form a shell in advance, blocking the pores of the braid.

[0028] In this embodiment, step S3 includes: loading the C / C billet and the premix into the second mold, so that the premix completely encapsulates the C / C billet, and then performing a second heat treatment to obtain a low-density impact-resistant C / SiC ceramic composite material.

[0029] The second mold is a graphite tooling mold.

[0030] The second heat treatment process includes: heating to 1400-1800℃ at a heating rate of 8-10℃ / min and holding at that temperature for 60-120 min; during the second heat treatment, a protective atmosphere is introduced. This invention does not limit the type of protective atmosphere, and those skilled in the art can select it according to the actual situation. For example, the protective atmosphere can be nitrogen or argon. In this process, the melt formed by the premixed material infiltrates into the porous structure of the C / C billet through capillary force to react, obtaining a C / C-SiC / ZrC / SiO2 composite material.

[0031] More preferably, the protective atmosphere is introduced at a rate of 0.5 to 1.5 L / min, and the furnace is kept under a slightly positive pressure (2 to 7 kPa).

[0032] In a second aspect, the present invention provides a low-density impact-resistant C / SiC ceramic composite material, which is obtained by the preparation method of the low-density impact-resistant C / SiC ceramic composite material provided in the first aspect of the present invention.

[0033] The material prepared by this invention exhibits high impact toughness (≥50kJ / m) after high and low temperature cycling. 2 It exhibits high tensile strength (≥260MPa) and good thermal conductivity (≥3W / m·k). Under high-temperature conditions, the material exhibits ductile fracture upon impact, with appropriate interfacial bonding between the matrix and the reinforcing phase. The uniform distribution of matrix grains hinders crack propagation, thus improving the material's toughness.

[0034] Example 1 1. Preparation of carbon fiber braided fabric The carbon fiber braided body adopts a stitched structure, as shown in the schematic diagram. Figure 1The woven fabric requires a layer of SYT45-6K carbon fiber cloth combined with a layer of ±60° carbon fiber mesh wound and laid up. The thickness direction uses single-strand SYT45-6K carbon fiber with bidirectional stitching, and the stitch spacing is 3×3mm. The density of the carbon fiber woven fabric is approximately 0.55g / cm³. 3 .

[0035] 2. Pretreatment (a) Mix carbon fiber braid and chitosan (molecular weight ≈ 30,000) at a mass ratio of 1:0.2; fix the mixture of carbon fiber braid and chitosan in a graphite tooling mold for fitting the surface, place the graphite tooling mold in an autoclave, apply 4 MPa atmospheric pressure in the autoclave, and slowly raise the temperature to 200°C to allow the molten chitosan to fully impregnate the carbon fiber braid and remain inside the carbon fiber braid; after the above hot pressing and shaping treatment, transfer it to the graphitization chamber, close the furnace door and evacuate to below 200 Pa.

[0036] (b) Introduce nitrogen gas until the vacuum level is above 95 kPa, close the gas filling valve, and evacuate again to below 200 Pa. Repeat this process 3 times. (c) Start heating, heating to 450℃ at a rate of 2.5℃ / min, heating to 1000℃ at a rate of 1.75℃ / min, heating to 1550℃ at a rate of 1.25℃ / min, heating to 2050℃ at a rate of 0.75℃ / min, and holding at that temperature for 150 min; during the heating process, argon gas is introduced at a flow rate of 1~2.5L / min until a slight positive pressure (2~5kPa) is reached inside the furnace, and the pressure inside the furnace is maintained at 2~5kPa.

[0037] (d) After the heat preservation is completed, maintain the pressure inside the furnace and cool it to 100°C with the furnace. Open the furnace and take out the material to obtain C / C billet.

[0038] 3. Preparation of premixed materials Silicon powder, chitosan (molecular weight ≈ 30,000), and zirconium carbide powder are ground evenly in a mortar at a mass ratio of 1:0.1:0.1, and then placed in an oven at 100℃ for 1.5 hours for later use.

[0039] 4. Positive pressure melt infiltration embedding molding The C / C billet was placed in a graphite tooling mold with a fitted surface, allowing the premix to encapsulate the entire C / C billet. The mass ratio of C / C billet to premix was 1:1.2. The graphite tooling mold was then placed in a tube furnace and heated at a rate of 9°C / min to 1600°C for 90 min. The melt was allowed to infiltrate into the porous material by capillary force and react. Subsequently, the furnace was cooled to room temperature to obtain a low-density, impact-resistant C / SiC ceramic composite material (C / C-SiC / ZrC / SiO2). During this process, argon gas was introduced into the furnace at a flow rate of 0.5~1.5 L / min, and the furnace was maintained under a slight positive pressure (2~5 kPa) until the material preparation was completed.

[0040] After implementing the above method, samples were taken from the same batch of flat plates for testing. The performance of the five groups of samples is shown in Table 1.

[0041] Density: GB / T 1463-2005; Impact toughness: GB / T1043.1-2008; Tensile strength: ASTM C1359; Thermal conductivity: GB / T 10295-2008.

[0042] Table 1. Properties of the materials prepared in Example 1

[0043] As can be seen from Table 1, the low-density impact-resistant C / SiC ceramic composite material prepared by the method in this embodiment has low density and high thermal conductivity, and exhibits good impact toughness at -70℃, 25℃ and 70℃, high tensile strength at 800℃, and low production fluctuation.

[0044] Five groups of flat plate samples prepared in the same batch were placed in a freezer at -70°C for 1 day, then removed and cooled to room temperature, and then placed in a 70°C oven for 1 day to return to room temperature. This was repeated 100 times before impact toughness and tensile strength tests were performed.

[0045] Table 2. Performance of the material prepared in Example 1 after 100 high and low temperature cycles.

[0046] As shown in Table 2, the low-density, impact-resistant, irregularly shaped C / SiC ceramic composite material prepared in this invention is insensitive to the effects of long-term high and low temperature cycling, and its material properties are basically stable, with the impact toughness remaining at 57 kJ / m. 2 The tensile strength is maintained above 270 MPa.

[0047] Example 2 1. Preparation of carbon fiber braided fabric The carbon fiber braided body employs a stitched structure. The braided body requires a layer of SYT45-6K carbon fiber fabric combined with a layer of ±60° carbon fiber mesh wound and laid up. In the thickness direction, SYT45-6K carbon fiber is used in a single strand, bidirectionally stitched, with a stitch spacing of 3×3mm. The density of the carbon fiber braided body is approximately 0.55 g / cm³. 3 .

[0048] 2. Pretreatment (a) Mix carbon fiber braid and chitosan (molecular weight ≈ 30,000) at a mass ratio of 1:0.1; fix the mixture of carbon fiber braid and chitosan in a graphite tooling mold for fitting the surface, place the graphite tooling mold in an autoclave, apply 3 MPa atmospheric pressure in the autoclave, and slowly raise the temperature to 220°C to allow the molten chitosan to fully impregnate the carbon fiber braid and remain inside the carbon fiber braid; after the above hot pressing and shaping treatment, transfer it to the graphitization chamber, close the furnace door and evacuate to below 200 Pa.

[0049] (b) Introduce nitrogen gas until the vacuum level is above 95 kPa, close the gas filling valve, and evacuate again to below 200 Pa. Repeat this process 3 times. (c) Start heating, heating at a rate of 2℃ / min to 400℃, heating at a rate of 1.5℃ / min to 950℃, heating at a rate of 1℃ / min to 1500℃, heating at a rate of 0.5℃ / min to 2000℃, and holding at that temperature for 150 min; during the heating process, argon gas is introduced at a flow rate of 1~2.5L / min until a slight positive pressure (2~5kPa) is reached inside the furnace, and the pressure inside the furnace is maintained at 2~5kPa.

[0050] (d) After the heat preservation is completed, maintain the pressure inside the furnace and cool it to 100°C with the furnace. Open the furnace and take out the material to obtain C / C billet.

[0051] 3. Preparation of premixed materials Silicon powder, chitosan (molecular weight ≈ 30,000), and zirconium carbide powder are ground evenly in a mortar at a mass ratio of 1:0.05:0.05, and then placed in an oven at 100℃ for 1.5 hours for later use.

[0052] 4. Positive pressure melt infiltration embedding molding The C / C billet was placed in a graphite tooling mold with a fitted surface, allowing the premix to encapsulate the entire C / C billet. The mass ratio of C / C billet to premix was 1:1.1. The graphite tooling mold was then placed in a tube furnace and heated at a rate of 8°C / min to 1500°C for 90 min. The melt infiltrated into the porous body by capillary force. Subsequently, the furnace was cooled to room temperature, and the reaction yielded a low-density, impact-resistant C / SiC ceramic composite material (C / C-SiC / ZrC / SiO2). During this process, argon gas was introduced into the furnace at a flow rate of 0.5~1.5 L / min, and a slightly positive pressure (2~5 kPa) was maintained inside the furnace until the material preparation was completed.

[0053] After implementing the above method, the same method as in Example 1 was used for testing. The performance of the five groups of flat plate samples from the same batch is shown in Tables 3-4.

[0054] Table 3. Properties of the materials prepared in Example 2

[0055] Table 4. Performance of the material prepared in Example 2 after 100 high and low temperature cycles.

[0056] Example 3 1. Preparation of carbon fiber braided fabric The carbon fiber braided body employs a stitched structure. The braided body requires a layer of SYT45-6K carbon fiber fabric combined with a layer of ±60° carbon fiber mesh wound and laid up. In the thickness direction, SYT45-6K carbon fiber is used in a single strand, bidirectionally stitched, with a stitch spacing of 3×3mm. The density of the carbon fiber braided body is approximately 0.55g / cm³. 3 .

[0057] 2. Pretreatment (a) Mix carbon fiber braid and chitosan (molecular weight ≈ 30,000) at a mass ratio of 1:0.3; fix the mixture of carbon fiber braid and chitosan in a graphite tooling mold for fitting the surface, place the graphite tooling mold in an autoclave, apply 4 MPa atmospheric pressure in the autoclave, and slowly raise the temperature to 200°C to allow the molten chitosan to fully impregnate the carbon fiber braid and remain inside the carbon fiber braid; after the above hot pressing and shaping treatment, transfer it to the graphitization chamber, close the furnace door and evacuate to below 200 Pa.

[0058] (b) Introduce nitrogen gas until the vacuum level is above 95 kPa, close the gas filling valve, and evacuate again to below 200 Pa. Repeat this process 3 times. (c) Start heating, heating at a rate of 3℃ / min to 500℃, heating at a rate of 2.0℃ / min to 1050℃, heating at a rate of 1.5℃ / min to 1600℃, heating at a rate of 1.0℃ / min to 2100℃, and holding at that temperature for 150 min; during the heating process, argon gas is introduced at a flow rate of 1~2.5L / min until a slight positive pressure (2~5kPa) is reached inside the furnace, and the pressure inside the furnace is maintained at 2~5kPa.

[0059] (d) After the heat preservation is completed, maintain the pressure inside the furnace and cool it to 100°C with the furnace. Open the furnace and take out the material to obtain C / C billet.

[0060] 3. Preparation of premixed materials Silicon powder, chitosan (molecular weight ≈ 30,000), and zirconium carbide powder are ground evenly in a mortar at a mass ratio of 1:0.15:0.15, and then placed in an oven at 100℃ for 1.5 hours for later use.

[0061] 4. Positive pressure melt infiltration embedding molding The C / C billet was placed in a graphite tooling mold with a fitted surface, allowing the premix to embed the entire C / C billet. The mass ratio of C / C billet to premix was 1:1.3. The graphite tooling mold was then placed in a tube furnace and heated at a rate of 10℃ / min to 1700℃ for 90 min. The melt was allowed to infiltrate into the porous body by capillary force and react. Subsequently, the furnace was cooled to room temperature to obtain a low-density, impact-resistant C / SiC ceramic composite material (C / C-SiC / ZrC / SiO2). During this process, argon gas was introduced into the furnace at a flow rate of 0.5~1.5 L / min, and the furnace was maintained under a slight positive pressure (2~5 kPa) until the material preparation was completed.

[0062] After implementing the above method, the same method as in Example 1 was used for testing. The performance of the five groups of flat plate samples from the same batch is shown in Tables 5 and 6.

[0063] Table 5. Properties of the materials prepared in Example 3

[0064] Table 6. Performance of the material prepared in Example 3 after 100 high and low temperature cycles.

[0065] As can be seen from Tables 3-6, the low-density, impact-resistant, irregularly shaped C / SiC ceramic composite materials prepared by using the method of the present invention and adjusting the process parameters within the scope of the present invention all have low density, good impact toughness, tensile strength and thermal conductivity.

[0066] Comparative Example 1 1. Preparation of carbon fiber braided fabric The carbon fiber braided body employs a stitched structure. The braided body requires a layer of SYT45-6K carbon fiber fabric combined with a layer of ±60° carbon fiber mesh wound and laid up. In the thickness direction, SYT45-6K carbon fiber is used in a single strand, bidirectionally stitched, with a stitch spacing of 3×3mm. The density of the carbon fiber braided body is approximately 0.55 g / cm³. 3 .

[0067] 2. Pretreatment (a) The carbon fiber braid is treated with furanyl ketone resin (density 1.1~1.3 g / cm³). 3 Impregnate at a mass ratio of 1:20; then cure at 210℃ for 1 hour and carbonize at 800℃ for 1.5 hours under nitrogen protection; subsequently place in a graphitization chamber, close the furnace door and evacuate to below 200Pa.

[0068] (b) Introduce nitrogen gas until the vacuum level is above 95 kPa, close the gas filling valve, and evacuate again to below 200 Pa. Repeat this process 3 times. (c) Start heating, heating to 450℃ at a rate of 2.5℃ / min, heating to 1000℃ at a rate of 1.75℃ / min, heating to 1550℃ at a rate of 1.25℃ / min, heating to 2050℃ at a rate of 0.75℃ / min, and holding at that temperature for 150 min; during the heating process, argon gas is introduced at a flow rate of 1~2.5L / min until a slight positive pressure (2~5kPa) is reached inside the furnace, and the pressure inside the furnace is maintained at 2~5kPa.

[0069] (d) After the heat preservation is completed, maintain the pressure inside the furnace and cool it to 100°C with the furnace. Open the furnace and take out the material to obtain C / C billet.

[0070] 3. Preparation of premixed materials Grind silicon powder and silicon carbide powder in a mortar at a mass ratio of 1:2 until uniform, then place in an oven at 100℃ for 1.5 hours for later use.

[0071] 4. Positive pressure melt infiltration embedding molding The C / C billet was placed in a graphite tooling mold with a fitted surface, so that the premixed material embedded the entire C / C billet. The mass ratio of C / C billet to premixed material was 1:1.2. The graphite tooling mold was placed in a tube furnace and heated at a heating rate of 9℃ / min to 1600℃ and held for 90 min. The melt infiltrated into the porous body by capillary force and reacted. Then, it was cooled to room temperature with the furnace to obtain the C / C-SiC composite material. During this process, argon gas was introduced into the furnace at a flow rate of 0.5~1.5L / min, and a slightly positive pressure (2~5kPa) was maintained in the furnace until the material preparation was completed.

[0072] After implementing the above method, the same method as in Example 1 was used for testing. The performance of the five groups of flat plate samples from the same batch is shown in Table 7.

[0073] Table 7 Material properties of Comparative Example 1 (Melted C / SiC)

[0074] As can be seen from Table 7, compared with Examples 1-3, the impact toughness, tensile strength and thermal conductivity of the melt-infiltrated C / SiC prepared by the conventional process in Comparative Example 1 are significantly lower.

[0075] Comparative Example 2 Compared with Example 1, the only difference is that chitosan was not added in step 2.

[0076] Comparative Example 3 Compared with Example 1, the only difference is that in step 2, the mass ratio of carbon fiber braid to chitosan is 1:1.

[0077] Comparative Example 4 Compared with Example 1, the only difference is that in step 3, the mass ratio of silicon powder to chitosan is 1:0.01.

[0078] Comparative Example 5 Compared with Example 1, the only difference is that in step 3, the mass ratio of silicon powder to chitosan is 1:1.

[0079] The performance of the samples prepared in Comparative Examples 2-5 was tested using the method described in Example 1. The test results are shown in Tables 8-9. The test results are the average values ​​of the five groups of flat plate samples prepared in the same batch.

[0080] Table 8. Properties of materials prepared in Comparative Examples 2-5

[0081] Table 9. Performance of the materials prepared in Comparative Examples 2-5 after 100 cycles of high and low temperature cycling.

[0082] As shown in Tables 8-9, the impact toughness and tensile strength of the materials prepared by the methods of Comparative Examples 2-5 of the present invention are significantly worse than those of Examples 1-3, but the impact toughness and thermal conductivity are still significantly better than those of Comparative Example 1, and the decrease in tensile strength is not significant.

[0083] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a low-density, impact-resistant C / SiC ceramic composite material, characterized in that, Includes the following steps: S1. Provides carbon fiber braided fabric and premixed material composed of silicon powder, first chitosan and zirconium carbide powder; S2. The carbon fiber braid and the second chitosan are mixed and then pretreated to obtain a C / C preform; S3. Using the C / C billet and the premix as raw materials, a low-density, impact-resistant C / SiC ceramic composite material is obtained by reactive melting infiltration.

2. The method for preparing the low-density impact-resistant C / SiC ceramic composite material according to claim 1, characterized in that, The molecular weight range of the first chitosan and the second chitosan is 20,000 to 50,000; and / or, The density of the carbon fiber braid is 0.55~0.75 g / cm³. 3 .

3. The method for preparing the low-density impact-resistant C / SiC ceramic composite material according to claim 1, characterized in that, In the premix, the mass ratio of silica powder to the first chitosan is 1:(0.05~0.15); and / or, In the premix, the mass ratio of silicon powder to zirconium carbide powder is 1:(0.05~0.15).

4. The method for preparing the low-density impact-resistant C / SiC ceramic composite material according to claim 1, characterized in that, The mass ratio of the carbon fiber braid to the second chitosan is 1:(0.1~0.3).

5. The method for preparing the low-density impact-resistant C / SiC ceramic composite material according to claim 1, characterized in that, Its features are, Step S2 includes: mixing the carbon fiber braid and the second chitosan, followed by hot pressing and a first heat treatment to obtain a C / C preform.

6. The method for preparing the low-density impact-resistant C / SiC ceramic composite material according to claim 5, characterized in that, The hot-pressing process includes: fixing the mixture of the carbon fiber braid and the second chitosan in a first mold, applying a pressure of 3-6 MPa, and slowly heating to 200-220°C, so that the molten second chitosan fully impregnates the carbon fiber braid and remains inside the carbon fiber braid; and / or, The first heat treatment process includes: heating to 400-500℃ at a heating rate of 2-3℃ / min, heating to 950-1050℃ at a heating rate of 1.5-2.0℃ / min, heating to 1500-1600℃ at a heating rate of 1.0-1.5℃ / min, heating to 2000-2100℃ at a heating rate of 0.5-1.0℃ / min, and holding at that temperature for 140-160 min; and / or, During the first heat treatment process, a protective atmosphere is introduced, and the furnace pressure is 2~7 kPa; and / or, Prior to the first heat treatment, the process also includes alternating vacuuming and the introduction of a protective atmosphere.

7. The method for preparing the low-density impact-resistant C / SiC ceramic composite material according to claim 1, characterized in that, The mass ratio of the C / C billet to the premix is ​​1:(1.1~1.3).

8. The method for preparing the low-density impact-resistant C / SiC ceramic composite material according to claim 1, characterized in that, Its features are, Step S3 includes: loading the C / C billet and the premix into a second mold, so that the premix completely encapsulates the C / C billet, and then performing a second heat treatment to obtain a low-density impact-resistant C / SiC ceramic composite material.

9. The method for preparing the low-density impact-resistant C / SiC ceramic composite material according to claim 8, characterized in that, The second heat treatment process includes: heating to 1400-1800℃ at a heating rate of 8-10℃ / min and holding at that temperature for 60-120 min; and / or, During the second heat treatment process, a protective atmosphere is introduced, and the furnace pressure is 2~7 kPa.

10. A low-density, impact-resistant C / SiC ceramic composite material, characterized in that, The low-density impact-resistant C / SiC ceramic composite material is obtained by the preparation method of the low-density impact-resistant C / SiC ceramic composite material according to any one of claims 1 to 9.